Overcoming biomass recalcitrance for enhancing sugar production from fast pyrolysis of biomass by microwave pretreatment in glycerol. Issue 2 (21st November 2014) - Zheng, Anqing; Zhao, Zengli; Huang, Zhen; Zhao, Kun; Wei, Guoqiang; Jiang, Liqun; Wang, Xiaobo; He, Fang; Li, Haibin
Abstract : Microwave pretreatment can selectively remove AAEM, lignin and hemicellulose fractions for enhancing levoglucosan yield from fast pyrolysis of pretreated corncob. Abstract : Levoglucosan, mainly derived from cellulose fast pyrolysis, is a versatile precursor to fuels, pharmaceuticals, and other value-added chemicals. However, biomass fast pyrolysis produces a very low amount of levoglucosan when compared to the theoretical yield based on cellulose fraction. Microwave pretreatment of biomass in glycerol is a potential pretreatment method prior to fast pyrolysis for enhancing levoglucosan yield since it can achieve the rapid heating and specific molecular activations for promoting the delignification and demineralization of biomass. In order to examine the validity of the pretreatment method, pretreatment of corncob in glycerol was conducted in a microwave reactor under ambient pressure. The pretreated corncobs were subsequently fast pyrolyzed in a semi-batch pyroprobe reactor. The experimental results show that microwave pretreatment in glycerol can serve as an effective pretreatment method for improving the sugar yield. The levoglucosan yield from fast pyrolysis of corncob pretreated at 150 W for 18 min was about 189 times higher than that of raw corncob. It was mainly ascribed to the effective removal of alkali and alkaline earth metals during microwave pretreatment of corncob in glycerol. In addition, the selective removal of lignin and hemicellulose fractions of corncob during pretreatment also plays positive roles in enhancing the levoglucosan yield.